Insights on GABAergic Mechanism of PPD from Pivotal Studies of Brexanolone Injection and SAGE-217 [18E]. (May 2020) - Meltzer-Brody, Samantha; Deligiannidis, Kristina; Colquhoun, Helen; Gunduz-Bruce, Handan; Dray, Danielle; Kanes, Stephen
Abstract : INTRODUCTION: One proposed etiology of postpartum depression (PPD) involves dysfunctional GABAergic signaling. Brexanolone injection (BRX) and SAGE-217, two neuroactive steroid GABAA receptor positive allosteric modulators, have been evaluated in a total of 4 double-blind, randomized, placebo-controlled trials (RCTs). METHODS: Inclusion criteria: adult women, ⩽6 months postpartum, diagnosed with PPD, and a qualifying HAM-D total score (BRX Studies A and B, ≥26; BRX Study C, 20–25; SAGE-217, ≥26). BRX randomization: 1:1:1 BRX 90 ug/kg/h (BRX90): BRX 60 ug/kg/h: placebo in Study B and 1:1 BRX90: placebo in Studies A/C, as 60-hour infusions, with follow-up through Day 30. SAGE-217 randomization: 1:1 SAGE-217 30 mg capsules or placebo for 14 days, with 4 weeks follow-up. Primary endpoints were change in HAM-D total score at Hour 60 (BRX) or Day 15 (SAGE-217). Adverse events (AEs) were recorded throughout the studies. RESULTS: Both BRX90 and SAGE-217 achieved their primary endpoints ( P <.0001 and P =.0028 respectively). Significant improvements versus placebo were sustained through Day 30 (BRX90, P =.0252) and Day 45 (SAGE-217, P =.0027). AEs in all BRX (n=140) occurring in ≥5% of BRX and ≥2x the rate of placebo were sedation/somnolence, dry mouth, loss of consciousness, and flushing/hot flush. The most common AEs (≥5%) with SAGE-217 were somnolence, headache, dizziness, upper respiratory tract infection, diarrhea, and sedation. CONCLUSION: BRX and SAGE-217 achieved their primary endpoints of statistically significant and clinically meaningful reductions in depressive symptoms versus placebo in PPD RCTs and were generally well tolerated. These results support the role of GABAergic signaling in PPD.